Pengaruh Integrasi Omnichannel terhadap Loyalitas Pelanggan pada Ritel Fashion Digital - Ariyadi, Catur; Safrudin, Safrudin; Ismaya, Lulut (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The rapid digital transformation in the Indonesian retail sector has prompted fashion retailers to adopt omnichannel strategies that integrate physical and digital channels. This study examines the effect of omnichannel integration quality on customer loyalty, with customer satisfaction as a mediating variable, within the context of digital fashion retail. Drawing upon the Stimulus-Organism-Response (S-O-R) framework, this research employs a quantitative approach with a sample of 200 omnichannel fashion consumers in Indonesia. Data analysis utilizes Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that omnichannel integration quality positively and significantly affects customer satisfaction and customer loyalty. Furthermore, customer satisfaction mediates the relationship between omnichannel integration and customer loyalty. These results underscore the strategic importance of seamless channel integration in fostering customer loyalty in the increasingly competitive digital fashion retail landscape.